Tindakan Supervisi dan Kepuasan Kerja Akuntan Pemula di Kantor Akuntan Publik - Nur Indriantoro; Myrna Nurahma (The Indonesian Journal of Accounting Research, 2013)
The Accounting Education Change Commission released its Issues Statement No.4 addressing concerns with the early employment experiences of professional accountants. Among other suggestions, the Commission recommended a number of actions supervisors of entry-level staff can employ to improve job satisfaction. This study reports the results of a survey of 97 entry-level accountants from 57 local, national and Big 5 accounting firms relative to their perceptions of the existence of the supervisory actions. This study finds that the three major elements of supervisory action recommended by the AECC, leadership and mentoring, working conditions, and assignments, are all correlated with reported job satisfaction. However, there are significant differences between small firms and Big 5 firms relative to both working conditions actions and job satisfaction, with accountants at smaller firms reporting higher levels of each.